(untitled) (Journal of Geography and Environmental Management, 2016)
The Loweramudarya economic region of Uzbekistan peculiarities and changes in the territorial structure of economy have been analysed, the area economic axis, factorial and Christallerian regular placing schemes interaction, forming clusters, region poles and growth lines have been defined in the paper. The growth of productive forces concentration in nodes and along lines has been predicted.